2014
DOI: 10.1097/nne.0000000000000033
|View full text |Cite
|
Sign up to set email alerts
|

Using Problem-Based Learning to Teach Health Policy at the DNP Level

Abstract: Nursing education recognizes the importance of graduate nurses understanding their roles as advocates, developers, implementers, and evaluators of health policies to impact the delivery of safe, patient-centered care. This article describes the use of problem-based learning as one approach to DNP health policy education. Students select a health problem and an associated health policy and use evidence-based practice, scholarly writing, and health services research to analyze the policy for efficiency, effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…PBL has been shown to provide a constructive environment for students to critically think and apply theories and concepts discussed in the clinical scenario, allowing for autonomy and application to real-world scenarios. 8 This pedagogical approach requires active participation from the student, often in small groups, and allows for selfdirected problem solving. Students who engage in the PBL curriculum versus traditional curricula had enhanced clinical reasoning and problem-solving skills, were more enthusiastic learners, and were better at self-directed learning.…”
Section: Problem-based Learningmentioning
confidence: 99%
“…PBL has been shown to provide a constructive environment for students to critically think and apply theories and concepts discussed in the clinical scenario, allowing for autonomy and application to real-world scenarios. 8 This pedagogical approach requires active participation from the student, often in small groups, and allows for selfdirected problem solving. Students who engage in the PBL curriculum versus traditional curricula had enhanced clinical reasoning and problem-solving skills, were more enthusiastic learners, and were better at self-directed learning.…”
Section: Problem-based Learningmentioning
confidence: 99%
“…For example, the analysis of graduate courses of health policy and systems research and analysis offered in 11 European and African countries concluded that traditional lecturing was the most common teaching strategies, while role playing was among the least employed teaching strategy (Erasmus et al, 2016). Thus, several studies have called for moving away from traditional teaching to active, practice-based and problem-based learning (Deon Kidd et al, 2016; Hayne & Schlosser, 2014). Indeed, a recent systematic review of health policy training documented the need and importance of experiential learning strategies as part of health policy education, as well as policy-related skills development such as writing policy-specific documents (Heiman et al, 2015).…”
Section: Health Policymentioning
confidence: 99%
“…As a response, and given the significance of health policy literacy, a few academics have employed active learning strategies in teaching health policy such as debates (Godinho et al, 2019), service learning (O’Brien-Larivée, 2011; Van Hoover, 2015) and role playing (Craig & Bloomfield, 2006). Specifically, the use of experiential learning in health policy education took several forms (Craig & Bloomfield, 2006; Godinho et al, 2019; Hayne & Schlosser, 2014; Krueger et al, 2011). In Malaysia, Godinho and colleagues (2019) documented their experience with debating evidence-based policymaking to develop competencies for evaluating debates in health professions (Godinho et al, 2019).…”
Section: Health Policymentioning
confidence: 99%
See 1 more Smart Citation
“…Recommendations for the amount of time and attention allotted to teaching health policy vary from health policy content being taught in standalone courses (Aduddell & Dorman, 2010; Ellenbecker et al., 2005; Harrington, Crider, Benner, & Malone, 2005; Hayne & Schlosser, 2014; Manning & Grasso, 2011; Nannini, 2009; O’Brien-Larivee, 2011) to it being integrated into content of existing courses (Cohen & Milone-Nuzzo, 2001; Hahn, 2010). Frequently recommended classroom strategies include debates on health policy issues, case study analyses, and mock committee testimonies.…”
Section: Introductionmentioning
confidence: 99%